Effect of Maternal Advanced Endometriosis on Risk of Congenital Malformations for Infants Born After in vitro Fertilization and Frozen–Thawed Embryo Transfer: Analysis of 28,600 Newborns - Liang, Zhou; Yin, Mingru; Ma, Meng; Wang, Yun; Kuang, Yanping (Frontiers in Endocrinology, 2019)
Background: Endometriosis is one of the most challenging diseases for doctors helping infertile women conceive, which has become a common method to help maternal endometriosis-associated infertility. Women with advanced endometriosis possess a higher risk of several adverse outcomes both during pregnancy and at the time of delivery. Whether endometriosis gives rise to a higher occurrence of congenital abnormalities in infants via in vitro fertilization and frozen–thawed embryo transfer (IVF-ET) remains unknown. Methods: Data collected on 22,865 women undergoing IVF using a freeze-all strategy from 2007 to 2017 were analyzed to estimate the rate of congenital malformations. We used an adjusted OR to compare the fertility outcomes of women with advanced endometriosis to the control group. Results: We studied 1,495 infants born from women with advanced endometriosis and 27,105 infants born from endometriosis-free women. There was a 1.557-fold risk that the infants with advanced maternal endometriosis would develop a congenital malformation (adjusted OR: 1.557, 95% CI: 1.03–2.35). Compared with singletons, twins were 1.957 times more likely to experience an adverse outcome (OR: 1.957, 95% CI: 1.561–2.455). When analyzing specific categories of birth defects, the proportion of circulatory system defects was higher than the other categories of birth defects in total (0.56%), followed by musculoskeletal system defects (0.15%). Conclusions: Maternal advanced endometriosis might increase the risk of congenital malformations for infants born after IVF-ET. The organ system most frequently affected by congenital malformations was the cardiovascular system, followed by the musculoskeletal system.